An urban experiment in small town sustainability in the UK: the case of Cittaslow - Susan Ball (Angles)
Member towns of the international network of slow cities are recent examples of the working out of development approaches that aim to involve local communities in the maintenance of the unique environmental and cultural heritage of individual locations. Formalised as Cittaslow, over the last two decades these towns are having to respond to a range of issues brought on by the increasing pace of life associated with globalisation and, conversely, stagnation due to being by-passed by footloose capital. The charter requirements of Cittaslow offer a means by which third-tier towns may address sustainable development. Having bought into the ideas for action promoted by Cittaslow International, ten towns in the UK have worked towards developing support in the community for a package of complex, connected technical measures. They have done so over a period marked by a shift from government to governance, and in an economic climate characterised by austerity. Evidence from local government officers points to the challenges of maintaining support for a view of sustainable development formulated elsewhere and which many people find hard to grasp. Quality of life and local uniqueness are nonetheless broad goals, around which communities can be anticipated to continue to organise in processes of governance for sustainable development.